Conflitos e saberes no início da carreira de professores de ciência e biologia - Guarany, Ann Letícia Aragão (2013)
The beginning of teaching is featured like an important period for the development constitution of a teaching carrier. It is a discovery moment but also a frustration moment conflicts will appear, and they are related to the teaching, like the attempts to minimize and face it. This research attempt to understand the Natural Science teachers face the conflicts in the beginning of professional carrier and how this processes of bearding contributes to the construction of teaching practice. To raise the objectives, personal interviews had been done with teachers of Science and Biology in the beginning of the carrier, that related the professional and personal history and furthermore a focal group had been created where collectively the members discussed about this particular moment in the carrier. According to the speeches and reports gave by the teachers we could comprehend how the teacher try to build your professional identity and reinforce your practice. Between the identified conflicts some of then where generated by relation with the subjects, with instruction, and related to curriculum, routines, and guidelines of the institutions they are bound to, also paper conflicts. To face it they utilize strategies that can be the conflict denial, the based in punctual actions coming up to the one that show conceptual change about the educative process. The sources used in this process are various, but mainly it starts from the history of life, of student and the practice experience of this teacher. Between the mobilized knowledge to face your main conflicts we can contrast the experiential acquired in the practice of your activity, and with it too. Starting from this job, we can identify competences too in this competences we can base the programs of formation, that seems to gave a low contribution in the moment that the new teacher begins your practice, furthermore contribute to the comprehend of some anxieties lived in the beginning of your carrier, which give voices to this that fell so many isolates in this search for the development and professional consolidations.